PERHITUNGAN HARGA POKOK JASA REPARASI DOCKING KAPAL PADA PT. KLASAMAN INDAH RAYA - JEMMY POANDY; Dewi Agustina; Hesty Rurusempo (LPPM Politeknik Saint Paul Sorong, 2021)
The cost of an amount of expenses and charges be permitted, either directly or indirectly to produce goods or services in the state and the place where the goods it has can be sold or used. calculation of the cost must be done properly and rationally as it affects the profit / loss of the company. If the cost is too high, the company will be difficult to compete, otherwise the cost is too low, the company then the company will be difficult to lose. The purpose of this study was to determine and analyze the calculation of the cost repair the ship docking at PT.Klasaman Indah Raya. This research uses case study method steps are carried out is to collect materials and data related, subject matter through the documentation, interviews and literature. Results of the study showed that the company melekukan calculation of the cost at the end of the year by collecting fees. But the company did not include overhead costs (BOP) in the calculation of the basic price, the research because it will be calculated the cost by incorporating smua costs, including overhead costs for each ship cost price calculation is done by order cost method. From the analysis of the calculations in this research note the cost for the two ships, namely the cost of KMP-NWRP.235.690.088 and the cost of KM-EVER RP.198.197.987